Medical Therapy of Acromegaly - U. Plöckinger (International Journal of Endocrinology)
This paper outlines the present status of medical therapy of acromegaly. Indications for permanent postoperative treatment, postirradiation treamtent to bridge the interval until remission as well as primary medical therapy are elaborated. Therapeutic efficacy of the different available drugs—somatostatin receptor ligands (SRLs), dopamine agonists, and the GH antagonist Pegvisomant—is discussed, as are the indications for and efficacy of their respective combinations. Information on their mechanism of action, and some pharmakokinetic data are included. Special emphasis is given to the difficulties to define remission criteria of acromegaly due to technical assay problems. An algorithm for medical therapy in acromegaly is provided.